A pilot community‐based randomized comparison of speech generating devices and the picture exchange communication system for children diagnosed with autism spectrum disorder. Issue 12 (26th November 2018) - Gilroy, Shawn P.; Leader, Geraldine; McCleery, Joseph P.
Abstract : A pilot community‐based randomized controlled trial was conducted to compare the effects of the Picture Exchange Communication System (PECS) to a teaching sequence using a high‐tech Speech Generating Device (SGD) to teach social communication behaviors. The two approaches were compared to evaluate the effectiveness of the newer, more high‐tech intervention using technology to improve social and communicative behavior of children diagnosed with Autism Spectrum Disorder. A total of 35 school‐age children were randomized to either a high‐tech (SGD device) or low‐tech (PECS cards) form of Augmentative and Alternative Communication (AAC). Study participants received 4 months of communication training delivered in their classrooms, and the primary outcome measures of the trial were several functional communication skills emphasized in the PECS teaching sequence. Results indicated that both high‐tech and low‐tech AAC approaches resulted in significant improvements in communication, and that these improvements did not differ significantly between the two approaches. These findings support the use of high‐tech AAC, and highlight the need for evidence‐based guidelines for its use as well as evaluation with individuals with a range impairments and disabilities. Autism Research 2018, 11: 1701–1711 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study compared the effectiveness of a free and open‐source app for teaching social and communicative behavior to children with autism spectrum disorder (ASD) to traditional picture card approaches. Thirty‐five children with ASD were randomized to a picture card or app‐based intervention and both treatment approaches resulted in significant improvements in social and communicative behavior. These data indicated that both "high‐tech" and "low‐tech" interventions were effective for improving behavior and that there was not a significant difference between the two approaches.